Building A Training Programme On The Dimensions Of Accountants' Professional Motivation And Its Impact On The Development Of Technical Literacy - Mohammed Kadhim Al-Abboodi; Mondher Fakhfakh (International Forum of Researchers and Lecturers, 2024)
The research aims to build a training programme according to the dimensions of the professional motivation of accountants and its impact on the development of technical Literacy by verifying the validity of the following null hypothesis: